2012
DOI: 10.1097/qad.0b013e32834f9d7c
|View full text |Cite
|
Sign up to set email alerts
|

Less decrease in risk behaviour from pre-HIV to post-HIV seroconversion among MSM in the combination antiretroviral therapy era compared with the pre-combination antiretroviral therapy era

Abstract: This study provides evidence that recently seroconverted MSM reduce their sexual risk behaviour following HIV diagnosis both in the pre-cART as well as the cART period. However, in the cART period this reduction in sexual risk behaviour is less and returns to pre-cART levels within 4 years. These findings not only confirm the need for early HIV testing but also make it clear that much more effort should go into identifying, counselling, and possibly treating recently seroconverted MSM who have been found to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
42
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 26 publications
6
42
0
Order By: Relevance
“…Identification of HIV infection during the acute phase of infection provides an opportunity to significantly reduce the risk of HIV transmission by providing education, safer-sex counseling, enrollment in care, and in some cases, initiation of antiretroviral therapy at a time when transmission risk may be greatest (7, 21-23, 39, 47). An accurate diagnosis of acute HIV infection is particularly relevant, as the impact of pre-and posttest counseling on risk behaviors may be eroding (20). Inclusion of the HIV p24 antigen in 4th-generation assays like the HIV Combo assay does allow the detection of some persons with acute HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of HIV infection during the acute phase of infection provides an opportunity to significantly reduce the risk of HIV transmission by providing education, safer-sex counseling, enrollment in care, and in some cases, initiation of antiretroviral therapy at a time when transmission risk may be greatest (7, 21-23, 39, 47). An accurate diagnosis of acute HIV infection is particularly relevant, as the impact of pre-and posttest counseling on risk behaviors may be eroding (20). Inclusion of the HIV p24 antigen in 4th-generation assays like the HIV Combo assay does allow the detection of some persons with acute HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Although being diagnosed with HIV has been associated with a significant reduction in sexual risk behavior, 1-3 a substantial minority of PLHIV continue to engage in unprotected sex. [4][5][6][7] Others may decrease sexual risk behavior immediately after diagnosis but show a rebound in these behaviors in subsequent months or years. For example, one study of men who have sex with men (MSM) who were recently infected with HIV found that the percentage of unprotected sex with unknown serostatus partners decreased from 49% at baseline to 25% at 6 months, but then rebounded to 71% at 12 months.…”
Section: Introductionmentioning
confidence: 99%
“…2 Another study that followed trends in sexual behavior pre-and post-HIV diagnosis found a 53% probability of unprotected sex at 1 year after diagnosis, but an increase to 61% 4 years after diagnosis. 5 Ongoing efforts to identify those factors that promote safer sexual behaviors between PLHIV and their partners are needed. Serostatus disclosure is fundamental to our understanding of the experience of HIV as an illness, because of its connection to privacy, ethical responsibility, and its possible function in prevention of disease transmission risk.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 These strategies seem promising in altering the HIV epidemic, but are under debate due to some observations of high-risk populations having low levels of risk perception, 29 and HIV-positive patients increasing risky sexual behaviors in the HAART era. [30][31][32][33] Previous studies have shown that under regular medical care, HIV-positive patients decrease their sexual risk behaviors by 30-55%, 30,33 especially in the initial years following the 158 CHENG ET AL.…”
Section: Discussionmentioning
confidence: 99%